The crystal structure of pyridinium diaqua-{1,2-phenylenebis((carboxylatocarbonyl)amido-κ4 N,N′,O,O′)manganese(III), C15H14MnN3O8 - Cao Zhen; Yan Wenhui (Zeitschrift für Kristallographie - New Crystal Structures)
C15H14MnN3O8, monoclinic, P21/m (no. 11), a = 7.3212(3) Å, b = 11.9120(4) Å, c = 9.3666(3) Å, β = 94.345(3)∘, V = 814.51(5) Å3, Z = 2, R gt(F) = 0.0242, wR ref(F 2) = 0.0685, T = 293 K.